Polychronicity, job performance, and work engagement: The mediating role of supervisor's organizational embodiment and moderation of psychological ownership - Naseem M. Twaissi; Omar M. Alhawtmeh; O'la Hmoud Al-Laymoun (Cogent Business & Management, 2022)
Despite its importance to the global economy and its role in generating foreign currency profits for many countries, the tourism industry is not without its share of problems. This calls for research on the causes of improved productivity in the workplace. Therefore, this study aimed to investigate the effect of polychronicity on job performance and work engagement of tourism employees. The supervisor's organizational embodiment was analyzed as a mediator and psychological ownership as a moderator. The data were gathered from 733 workers in the private tourist facilities of the city of Petra, Jordan by using a structured questionnaire and data analysis was carried out using AMOS-24. The findings revealed that polychronicity can lead to better job performance and work engagement. Supervisor's organizational embodiment positively mediates the relationship of polychronicity with job performance and work engagement. In addition, the psychological ownership strengthens the relationship of polychronicity with work engagement and job performance. The emphasis of this study is on the most important behavioral outcomes of employees (i.e. work engagement and job performance); therefore, the practitioners of the tourism industry and hospitality industry can use the findings of this study to manage engagement- and performance-related issues of employees. Similarly, the researchers interested in polychromic behavior in organizations can also consider this research as a guideline.
Keywords: 650; job performance; Polychronicity; psychological ownership; supervisor's organizational embodiment; work engagement